KONSEP IDEAL PENDIDIKAN ISLAM PRESPEKTIF IMAM AL GHOZALI - Nur Iftitahul Husniyah; Nur Hakim Nur Salim (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Abu Hamid Muhammad bin Muhammad al-Ghazali or who is more famous in our ears as Imam al-Ghazali. Is a famous scholar in the archipelago with the science of Sufism. Al-Ghazali's background as a Sufi, worship expert, and prioritizing noble morals greatly influenced him in all his thoughts, including Islamic education. The journey of Islamic education which has grown and developed to date is strongly influenced by the thoughts of the driving figures in implementing the existing learning system in their educational institutions. There are three main streams of Islamic education, namely: conservative, religious-rational and pragmatic-instrumental. The purpose of this research is to conceptualize an ideal Islamic education so that it makes life perfect, namely perfect human beings as contained in Al-Ghazali's thoughts. According to Al-Ghazali the purpose of education is to get closer to Allah SWT, not to seek a position that generates money. According to al Ghazali, the material aspects of Islamic education include: faith, morals, reason, social and physical education. While the evaluation of education is all forms of activity related to the duties and responsibilities of each in the educational process. The research method in this research is a literature study or library research aimed at collecting information and data using various kinds of library instruments, both books, journals, files and others. Furthermore, the results of this study indicate that the ideal concept of Islamic education according to Al-Ghazali that the Ideal Islamic Education is Education based on the Al-Qur'an and Hadith. The findings from this study are that the components of an ideal Islamic education include educators who have noble character and students who are required to respect a teacher. Meanwhile, a good Islamic education curriculum according to Al-Ghazali is an Islamic education curriculum that emphasizes religious aspects or religiosity which has implications for use value in society, especially in the field of tasawuf and fiqh. In the context of an ideal evaluation of Islamic education, Imam Al-Ghazali emphasizes all aspects of mental, psychological and spiritual-religious life.